Canadian Archives: Patterns from a Federal Perspective - Taylor, Hugh A. (Archivaria, 1976)
During the 1974 annual meeting of the Society of American Archivists, a comparative session was held on national history documentation strategies. This session highlighted the pressing need for Canada to define a national archival strategy. The author first describes the main stages of the evolution of archives in Canada since New France. He then defines the scope of the role that the Public Archives of Canada intend to play within the Canadian archival network. The “total utilization” concept becomes the logical consequence of the Public Archives of Canada’s “total archives” concept, one that upholds that documentation from our past − no matter the medium − must not only be preserved but made available. In this way, the printing of historical documents cannot be neglected as it allows greater use and a better preservation of a greater number of media. The Public Archives of Canada have a special role to play and should take the lead in the creation of modern finding aids, the production of machine-readable archives, the dissemination of records, and giving aid to smaller archival repositories. The archivist must adapt to all media creating historical documentation. RÉSUMÉ Au cours de la réunion de la Society of American Archivists de 1974 une session comparative portant sur les stratégies de documentation de l'histoire nationale a mis à jour le besoin impératif pour le Canada de se définir une stratégie nationale de l'archivistique. Après avoir décrit les principales étapes de 1'évolution des archives au Canada depuis la Nouvelle-France, l'auteur s'attache à circonscrire le rô1e qu'entendent jouer les Archives publiques du Canada dans le réseau archivistique canadien. À partir du concept d’« archives complètes », auquel elles souscrivent, le concept d’« utilisation totale » devient un corollaire logique selon lequel la collection de documentation du passé, quelque en soit le médium, doit non seulement être préservée, mais également diffusée. Ainsi, la copie de documents historiques ne doit pas être négligée puisqu'elle permet une plus grande utilisation et une meilleure préservation d'un grand nombre de média. Les Archives publiques du Canada ont un rôle spécial à jouer et devraient prendre les devants dans la création d'instruments de recherches modernes, dans la miniaturisation, la diffusion et surtout l'aide aux dépôts plus modestes. L'archiviste doit ainsi s'adapter à tous les milieux créateurs de documentation historique.